"Y no quedó nada, nada de la casa, todo salió volando" (And there was nothing left, nothing of the house, everything flew away): a critical medical ecological perspective on the lived experience of hurricane María in Puerto Rico - D. Vega Ocasio; J. G. Pérez Ramos; T. D. V. Dye (BMC, 2021)
Abstract Background Ecological disasters create dramatic changes as man-made and natural ecosystems adapt to their effects. In 2017, Hurricanes Irma and María devastated Puerto Rico. Public focus after such traumatic ecological events often neglects pre-existing community dynamics, heterogeneity of lived experience, and complexity of decision-making in the disaster context. We intended to better understand the lived experience of this ecological trauma in communities across ecosystems in Puerto Rico and among those displaced to Florida. Method We used the Critical Medical Ecological (CME) framework to assess the relative contribution of ecological dimensions on lived experience across community levels and time. We used qualitative methods with emic coding and etic mapping of salient constructs to the ecological model. In total, 96 people participated in 23 discussion encounters. Two people coded interviews in Spanish using Dedoose. We identified common themes in sequential order mapped to elements of the CME to approximate the participants' temporal experience. Results Codes applied to the period of the hurricane's landfall, traverse, and exit were markedly distinct from the other two periods (before and after) examined in this study: the experience of the hurricane's strike was highly personal and, at this level, reflected a mix of sociocultural, biological, and abiotic factors. After the hurricanes, social and community factors re-emerged while new risks and conditions arose that were biological (e.g., leptospirosis, no food or water) or abiotic (e.g., unusable roads/bridges, structures destroyed), but created ongoing stressors and social needs for communities. As we found, the dynamics of the social and household landscape sometimes involved the decision to leave Puerto Rico altogether, or forced people to continually face and adapt to the ongoing collapse in basic services that were only slowly and differentially restored. Conclusion Lived experience across each stage of the hurricanes differed substantially from one another. Communities disrupted by ecological disaster are also frequently entangled within global economic and political histories and dependencies that could preclude recovery. Island nations are especially vulnerable to both climate-induced ecological change and political-economic exploitation. The ongoing health effect of the hurricane remains palpable in many communities of Puerto Rico and among the diaspora in Florida.